Republic of Kazakhstan : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessments Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2008)
The data quality assessment shows that Kazakhstan is in observance of the Special Data Dissemination Standard, meeting the specifications for coverage, periodicity, timeliness, and the dissemination of advance release calendars. Executive Directors have suggested a set of recommendations that are designed to further increase Kazakhstan's adherence to internationally accepted statistical practices and enhance the analytical usefulness of Kazakhstan's statistics. Cross-cutting recommendations, national accounts, consumer and producer price indices, government finance statistics, monetary statistics, and balance of payments statistics were reviewed for the recommendations.